Infective endocarditis in central South Africa in the HIV era- a surgical perspective - Gwila, Taha H. (University of the Free State, 2021)
Introduction: Infective endocarditis (IE) remains an evolving disease with a persistently high mortality and morbidity. In Africa, it is predominantly a disease of the young in contrast to the developed world. South Africa represents a very high prevalence of HIV at 21.67% of global HIV infections. Other factors in South Africa include the high prevalence of rheumatic valvular heart disease, low socio-economic status and poverty makes the patient population completely different from the developed world. The primary aim was to determine the influence of HIV infection on infective endocarditis patients in central South Africa. The secondary aim was to compare the HIV positive patients and HIV negative patients in the context of this disease. Objectives: To determine the demographics, presentation, indication for surgery, microorganisms, and outcomes of HIV positive versus HIV negative patients presenting with Infective endocarditis. Methods: Retrospective, analytical cohort study that reviewed the records of adult patients who were tested for HIV and treated surgically for infective endocarditis between 2009 to 2019. Data was compared between the two groups using chi-square or Fisher exact tests for categorical variables. Median and interquartile ranges were used for continuous variables and frequencies and proportions for categorical variables. Significance was set as p < 0.05. Results: From the 141 IE patients who underwent surgery for IE, 105 patients were tested for HIV, 31% (n=33) tested positive. The mean age for both groups was comparable 38.87 versus 39.51 years. Eighty-eight percent (n=29) of positive patients were on HAART. In both groups, there was a male preponderance, 55% vs 46% and 56% vs 44% respectively. The majority of HIV positive (91%) and negative patients (71%) were of African descent, more than 50% of both groups presented with NYHA III&IV, both groups had a medium-high risk of developing IE (HIV (+) 72%; HIV (-) 62%). Prevention of embolization was the main indication for surgery in HIV (+) group and heart failure in the negative group. In both groups a greater proportion of patients had left sided native valve endocarditis 95% and RHD was predominantly the underlying pathology 60%, requiring mechanical prostheses mainly in the mitral 46% and aortic 33% position. Right sided endocarditis represents <5% and only 2 out 105 patients confirmed IVDA’s, Staphylococcus and Streptococcus dominated cultured organisms with staphylococcus species being more frequent, culture negative endocarditis remains high in both groups, with 47% HIV (-) group vs 33%. Morbidity was limited in both groups 12% vs 11% with no major difference. The overall mortality was higher in the HIV (+) group (39% vs 34%); however, the in-hospital mortality was higher in the HIV (-) group (17% vs 12%). Conclusion: Infective endocarditis remains a deadly disease with high short- and long-term mortality. HIV infection has minimal to no impact on perioperative and in- hospital morbidity and mortality, left heart endocarditis is the dominant disease within the HIV patients due to the rheumatic valvular heart disease as opposed to right heart endocarditis. The high prevalence of culture negative endocarditis warrants further investigation. Given the low number of patients in this cohort study, further prospective studies need to be conducted to establish a statistical significance between the HIV (+) and (-) groups.
Dissertation (M.Med.(Cardiothoracic Surgery))--University of the Free State, 2021
Keywords: Infective Endocarditis; Cardiac surgery; Human immunodeficiency virus Etiology; Epidemiology; Microorganisms; Outcomes